PENGARUH LEVEL INOKULAN DAN LAMA INKUBASI OLEH Aspergillus niger TERHADAP KANDUNGAN NUTRISI PUTAK - M. A. Hilakore; . Suryahadi; IGK. Wiryawan; D. Mangunwijaya (Politeknik Pertanian Negeri Kupang, 2008)
The experiment used fermentation technique. Aspergillus niger was employed in attempting to increase the quality of putak. The experiment was arranged factorially using Completely Randomized Design 4 x 3. Factor A consisted of 4 levels of inoculants: 0.5, 1.0, 1.5, and 2.0% (w/w), while factor B consisted of incubation duration, that is 2, 3 and 4 days. Variables assessed were crude protein, true protein, crude fiber and dry matter contents of putak. The result showed that the treatments were significantly (P<0.05) affected the variables assessed. In conclusion, the treatments was improved the quality of putak. Keywords: putak, Aspergillus niger.